Delayed diagnosis of isolated coracoid fractures: results of 9 cases treated conservatively - Vaienti, E.; Pogliacomi, F. (Acta Biomedica Atenei Parmensis, 2012)
Background and aim: Isolated coracoid process fractures are more frequent than what has formerly been believed. Delayed diagnosis or misdiagnosis are not infrequent as it is difficult to notice this injury using routine radiographic projections of the shoulder. In any event, more specific views are prescribed only when a fracture is suspected. The purpose of this study is to assess the outcomes of 9 cases of isolated coracoids fractures treated conservatively after being undiagnosed and discuss the reasons of these delayed diagnoses. Materials and Methods: Between January 1984 and June 2011, 9 out of 19 isolated coracoid fractures received a delayed diagnosis. There were 7 type I fractures and 2 type II. All patients were treated conservatively. Results: All fractures, except one, consolidated. The delay of the diagnosis was greater in type II lesions rather than in type I. Differences in clinical outcomes between affected and healthy side were minimal. Delayed diagnosis was overseen by the physician in 8 cases whereas in 1 case the patient underestimated the trauma and left the injury untreated. Conclusions: An isolated coracoid fracture should always be suspected after receiving a direct blow on the shoulder or after sustaining a forceful traction of the upper arm. In these events, specific radiographic projections should be performed in order to visualise the entire length of the coracoid process and to avoid oversight, delayed diagnosis or misdiagnosis. In isolated type I undisplaced fractures and in the majority of type II fractures, conservative treatment is indicated.